2006
DOI: 10.1111/j.1365-2354.2005.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences of completing treatment for colorectal cancer in a Scottish District General Hospital

Abstract: A review of the cancer literature from 1990 to 2003 indicated that some patients with cancer felt abandoned by healthcare professionals upon completion of treatment. With this in mind, a small qualitative study was undertaken to explore the experiences of patients completing treatment for colorectal cancer within a Scottish District General Hospital. A small purposeful sample of eight participants (surgery only n = 4 and surgery with adjuvant chemotherapy n = 4) who had completed treatment were recruited. Semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 25 publications
(64 reference statements)
2
30
1
1
Order By: Relevance
“…Expectation of a cure after completing treatment was a natural outcome and the patients looked forward to live as usual. These experiences were in agreement with results in other studies of cancer patients [21,22]. In the present study the patients expressed doubts three months after they had finished chemotherapy.…”
Section: Discussionsupporting
confidence: 83%
“…Expectation of a cure after completing treatment was a natural outcome and the patients looked forward to live as usual. These experiences were in agreement with results in other studies of cancer patients [21,22]. In the present study the patients expressed doubts three months after they had finished chemotherapy.…”
Section: Discussionsupporting
confidence: 83%
“…3,23,24 Although others have identified the potential importance of the role of primary care in addressing physical, psychological, and social issues following a cancer diagnosis, 16,17 this study showed these needs to be unmet, and that patients often did not identify their GP as the main source of potential help in meeting such needs. Patients identified with their nurse specialist, with whom they had built a relationship.…”
Section: Strengths and Limitationsmentioning
confidence: 91%
“…Dose reduction could be one way to handle moderate or severe neurotoxicity under the treatment to improve the chance of therapeutic success and quality of life [3] [15]. Following the progression of the symptoms can improve the patient's quality of life [30] [31].…”
Section: Discussionmentioning
confidence: 99%